In search of educational agency with a territorial approach in urban school settings. Systematic review of investigative background - Diago Camacho, Juan Sebastián (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2022)
The following systematic review includes the revision of numerous scientific databases regarding the different conceptual links between human agency, educational quality in the school, and spatial/territorial approaches to urban schools. This with the purpose of identifying possible pedagogical and investigative scenarios that can contribute to the strengthening of the comprehensive approaches and practices of the different educational actors that meet in the public schools of the cities in our region.